A Study of the Morphological, Physical and Chemical Characteristics of Soils as Influenced by Teak Vegetation: 1 - Jose, A. I.; Koshy, M. M. (Indian Forester, 1972)
A study has been made of the forest soils of the Nilambur Division, Kerala State to determine the extent to which the properties of solis are affected by deforestation followed by the maintenance of a puse teak plantation. Profile sites were selected from natural forests and teak plantations of age 1, 15,30, 60 and 120 years. All the solis under study were of lateritic origin. Observations revealed that the morphological features of the soils had been altered by the silvicultural operations. A surface layer of decomposing organic matter was seen only in natural forest and the teak preservation plot of 120 years old. The variation in the organic matter content of soli at different depths was found correlated with the age of the teak plantation. The surface soils of young aged teak plantations exhibited remarkably higher values for apparent density and absohite specific gravity and relatively lower values for pore space, waterholding capacity and percentage volume expansion indicating that physical conditions of the soils bave been markedly altered as a result of deforestation and planting of teak. But these variations were well pronounced only up to a period of 30 years after planting. The physical properties of soils from the 120 year old teak preservation plot were comparable to that of the natural forests. However, considerable compaction of soil was noticed in the second rotation plots.